Anomaly Detection Framework for PingER Data - Danny Wilson, Mandai; Johari, Abdullah (Faculty of Computer Science and Information Technology, 2015)
The poster was submitted as part of the UNIMAS R&D Expo 2015. The project won Bronze Medal from the Expo for the ICT Cluster category.